Spinster is required for autophagic lysosome reformation and mTOR reactivation following starvation. - Rong, Y.; McPhee, C.; Deng, S.; Huang, L.; Chen, L.; Liu, M.; Tracy, K.; Baehreck, E.H.; Yu, L.; Lenardo, M.J. (Proceedings of the National Academy of Sciences of the United States of America, 2011)
Autophagy is a conserved cellular process to degrade and recycle cytoplasmic components. During autophagy, lysosomes fuse with an autophagosome to form an autolysosome. Sequestered components are degraded by lysosomal hydrolases and presumably released into the cytosol by lysosomal efflux permeases. Following starvation-induced autophagy, lysosome homeostasis is restored by autophagic lysosome reformation (ALR) requiring activation of the "target of rapamycin" (TOR) kinase. Spinster (Spin) encodes a putative lysosomal efflux permease with the hallmarks of a sugar transporter. Drosophila spin mutants accumulate lysosomal carbohydrates and enlarged lysosomes. Here we show that defects in spin lead to the accumulation of enlarged autolysosomes. We find that spin is essential for mTOR reactivation and lysosome reformation following prolonged starvation. Further, we demonstrate that the sugar transporter activity of Spin is essential for ALR.